AKAD MUSYARAKAH MUTANAQISAH DALAM SISTEM PERBANKAN SYARIAH - Muhammad Anwar Zainuddin (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2018)
The need for house is one of the primary needs for every human being and basic rights for humans. The financing of musyarakah mutanaqisah in the Islamic banking system is one of the bank's involvement in the provision of housing loans. Financing musyarakah syirkatul milk is the combination of capital from two or more people to finance a project / business, profits will be divided based on the proportion of capital; whereas if there is a loss it will be borne together according to the agreement contained in the contract / contract agreement. Islamic banking has obtained formal juridical legitimacy that strengthens sharia principles as a principle that underlies the operational system of profit-sharing banking activities. This is a concrete manifestation of the objective conditions of the Islamic community's need for Islamic institutions, which is believed to be an alternative solution for efforts to optimize the economic potential of the community.